IMPLEMENTASI SISTEM VERIFIKASI DIGITAL UNTUK PENCEGAHAN FRAUD PADA PROGRAM JKN (STUDI KASUS RS SYARIAH JAKARTA) - Gunadi, Papan; Hasan, Sabri; Arda, Ichria Nurul; Rahayu, Enoh Dwi; Andika, Zikra (Media Riset Bisnis Ekonomi Sains dan Terapan, 2024)
The importance of fraud prevention and management in Indonesia's National Health Insurance Program (JKN) is emphasized as part of the government's efforts to provide access to quality healthcare services. Fraud in healthcare services can harm the nation and reduce the quality of care. Therefore, fraud prevention becomes crucial, particularly through the establishment of a Fraud Prevention Team in healthcare facilities. Technological support, such as digital verification systems and artificial intelligence, is essential for enhancing efficiency in detecting and preventing fraud. A qualitative research method was employed to analyze the implementation of fraud prevention systems at the Islamic Hospital in Jakarta. The research findings show that the application of digital verification technology can improve accuracy, transparency, and accountability in managing health claims. This article concludes that this system has the potential to support the sustainability of the JKN program and enhance the integrity of healthcare services. Keywords : Fraud Prevention, National Health Insurance Program (JKN), Digital Verification